A long-term review of dermal grafts and bronchial reconstruction. Issue 3 (May 1973) - Monk, Ian
Abstract : Between 1953 and 1962, 21 patients presented with bronchial strictures. Bronchial reconstruction was carried out on 15 of these while a dermal graft was employed in another six patients. The follow-up period, therefore, is between 10 and 20 years. Bronchial structures lend themselves to satisfactory reconstruction. This review, however, showed that late contraction of a dermal graft may occur even two years after operation.